Penyuluhan pemanfaatan feses sapi sebagai briket bahan bakar alternatif - Purwanta Purwanta; Sarti Patontongan; Nuraeni Nuraeni (Universitas Negeri Makassar, 2019)
The partners in this community serviceactivityarethe Lantebung farmer group, Pakatto Village, Bontomarannu District in Gowa Regency. Their problems are 1). lack of knowledge, attitudes and skills of cattle farmers towards utilization of cattle feces as an alternative fuel with sago flour adhesives; 2) Cattle feces waste has not been used optimally becomes higher economic value product. The external target is cattle feces have a higher economic value after being processed into feces briquettes. The implementation and extension design includes the determination of material, methods, techniques, media, targets, implementations and evaluations. The result achieved are: 1) Improved partners knowledge, attitudes and skills to use of cattle feces into briquettes with sago flour adhesives. 2) Increased the economic value of cattle feces.